Membangun Keterampilan Menulis Berpikir Kreatif Untuk Mewujudkan Generasi Muda yang Berjiwa Wirausaha di Panti Asuhan Al-Yamin - W, Widia; M, Mainilawati; H, Hetilaniar (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Writing is an activity that turns ideas into expressions. According to the opinion (Dalman, 2020, p. 3) Writing is the use of written language as a medium for conveying information contained through writing to other parties. In writing, of course, we need what purpose we want to write and create as part of writing and in this case we do a writing procedure where we will do a project with children in the Al-Yamin orphanage to make writing the procedure for making beads into bracelets, necklaces, rings and cellphone straps from beads and given a strap. Beads are small pieces of jewelry that have a hole in the center to be attached to necklaces, bracelets and other skills. People who have creativity skills are always needed by the environment because they can overcome problems that continue to develop. The purpose of the activity is to foster an entrepreneurial spirit and creativity in children at the Al-yamin orphanage in Palembang in writing skills, procedures for making and producing products from projects that have been made. This service examines efforts to foster an entrepreneurial spirit and creativity about writing skills, managing beads into handicrafts with qualitative descriptive methods. The results of the posttest show that the children in the orphanage already have the character of an entrepreneurial spirit. The final results based on the results of the prettest and postes can be categorized as successful and satisfactory, the children in the orphanage are able to do several handicrafts according to the instructions.